Clinical and Biochemical Characteristics of Severe Hypothyroidism Due to Autoimmune Thyroiditis in Children - Kucharska, Anna Małgorzata; Witkowska-Sȩdek, Ewelina; Labochka, Dominika; Rumińska, Małgorzata (Frontiers in Endocrinology, 2020)
Introduction: In the majority of countries, autoimmune thyroiditis is the main cause of acquired hypothyroidism in children. Typically, the natural course of the disease is initially insidious and the diagnosis is incidental. There are some children who develop severe hypothyroidism without a proper diagnosis. The aim of the study was to analyze the clinical and biochemical profiles of children with severe primary hypothyroidism due to autoimmune thyroiditis. Materials and Methods: We analyzed the records of 354 patients diagnosed between 2009 and 2019 with autoimmune thyroiditis. Only patients with TSH above 100 μIU/mL, associated with decreased free thyroxine and the presence of antithyroid antibodies, were enrolled in the study. The analysis encompassed clinical symptoms, thyroid and biochemical status, bone age, and imaging. Results: Twenty-six children were enrolled in the study. The mean age at diagnosis was 10.26 ± 3.3 years, with a female preponderance of 1.8:1. The most frequent symptom was growth impairment (77%) and weight gain (58%). Goiters were present in 42% of patients. Less common findings were pituitary hypertrophy (four patients) and hypertrichosis (three patients). Median values at the time of diagnosis were TSH 454.3 uIU/ml (295.0–879.4), anti-TPO antibodies 1,090 IU/ml, and anti-Tg antibodies 195 IU/ml. Anti-TSHR ab were evaluated only in six out of the 26 patients. The characteristic biochemical profile was correlated with the grade of hypothyroidism, and the strongest correlations were found with CBC parameters, lipid profile, aminotransferases, and creatine. Conclusion: In children with severe hypothyroidism, the most sensitive symptoms are growth arrest and weight gain despite the fact that, in some children, the auxological parameters at presentation could be within normal values for the population. The specific biochemical profile closely correlates to the severity of thyroid hormone deficiency and involves mostly erythropoiesis, liver function, and kidney function. Pituitary enlargement should be considered in each child with severe hypothyroidism. It is necessary to conduct prospective studies evaluating the actual frequency of anti-TSHR antibodies and pituitary enlargement in children with extremely high TSH, especially those presenting without goiters.